Robust Finite Time Controller Design for Electronic Throttle Control System - Xiang, Hongbing; Chen, Gang (Chinese Automation Congress (Online), 2019)
Electronic throttle control system (ETCS) is nonlinear and complex, which is subject to gear backlash, transmission friction, limp-home spring set, external disturbances and uncertainties of some physical parameters. Therefore, it is a challenging task to control electronic throttle system. In order to achieve the satisfactory performance of ETCS, a finite-time sliding mode controller is investigated in this paper. Firstly, we proposed an adaptive finite time control strategy to obtain more precise tracking control of throttle valve. To avoid the discontinuity of control inputs, we further provide a continuous robust finite-time control strategy. It is proved that, under the proposed controllers, the throttle valve tracking error converges to a bounded region in finite time. Finally, two group of simulation results are provided to validate the effectiveness of the proposed control strategies.